3D atom microscopy in the presence of Doppler shift. (5th February 2018) - Rahmatullah,; Chuang, You-Lin; Lee, Ray-Kuang; Qamar, Sajid
Abstract: The interaction of hot atoms with laser fields produces a Doppler shift, which can severely affect the precise spatial measurement of an atom. We suggest an experimentally realizable scheme to address this issue in the three-dimensional position measurement of a single atom in vapors of rubidium atoms. A three-level Λ-type atom–field configuration is considered where a moving atom interacts with three orthogonal standing-wave laser fields and spatial information of the atom in 3D space is obtained via an upper-level population using a weak probe laser field. The atom moves with velocity v along the probe laser field, and due to the Doppler broadening the precision of the spatial information deteriorates significantly. It is found that via a microwave field, precision in the position measurement of a single hot rubidium atom can be attained, overcoming the limitation posed by the Doppler shift.